The Influence Of Inquiry-Stad Learning Strategies (Instad) Toward Science Process Skills And Student’s Achievement In Studying Biology - Yasir Sidiq; Puguh Karyanto; Bowo Sugiyarto (Universitas Sebelas Maret, 2012)
Aims of this research are to know the influence of INSTAD learning strategies toward sciences process skills and influence of INSTAD learning strategies toward student’s achievement in studying biology of SMA Batik 1 Surakarta. This research was quasi experiment research using quantitative approach. The research was designed using posttest only randomized control group by using the experimental classes (application of INSTAD strategy) and control classes (conventional learning). Population studies are all students of SMA Batik 1 Surakarta in academic year 2011/2012. Sampling techniques with cluster random sampling, so chosen X-5 as the experiment class and X-4 as the control class. Data was collected using questionnaire, essay test, observation sheet, and document. The data were analyzed by t-test.The conclusion of this research were science process skills was significantly affected by INSTAD and the application of INSTAD has taken effect on student’s cognitive and psychomotor, but hasn’t taken effect on student’s affective achievement in studying biology of SMA Batik 1 Surakarta. Key Words: INSTAD learning strategies, science process skills, biology student’s achievement